Evaluation of Genetic Diversity of QPM, Provit-A, and Elite Maize Inbreds Resistant to Downy Mildew Disease Using Simple Sequence Repeats - andayani, nining nurini; Isnaini, Muzdalifah; Aqil, Muhammad; Muis, Amran; Pabendon, Marcia Bunga; Azrai, Muhammad (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
Functional maize tends to be more susceptible to major maize diseases, particularly Downy mildew. Among the functional maize are Quality Protein Maize (QPM) and Provit A maize. The presence of higher amino acid and beta carotene in functional maize might have caused these types of maize more susceptible to Downy mildew disease. The objective of the research was to identify the heterotic pairs among maize inbreds i.e. QPM, Provit A, and local maize varieties resistant to Downy mildew disease using Simple Sequence Repeats (SSR) marker. The research was conducted from April to July 2017 at the Molecular Biology Laboratory of Indonesian Cereals Research Institute. A total of five QPM inbreds, 15 Provit A inbreds, and 11 Downy mildew resistant local varieties of maize were used in the experiment using 34 SSR markers. Results indicated that among 34 SSR locus analysed, variation of allele lengths ranged from 74 bp to 500 bp. A total of 125 alleles ranging from two to nine alleles per locus with an average of 3.68 alleles were generated. The data indicated wide genetic variations among characters. DNA band profile showed that nc130 marker produced the highest PIC (over 0.83) and allele value (8.00). Genetic distance analysis found a total of 21 heterotic genotypes with genetic distance exceeds 0.65.Â